ADVERSE EFFECT OF COMBINED ORAL CONTRACEPTIVE PILLS - Shukla, Akshara; Jamwal, Rohitash; Bala, Kumud (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Oral contraceptive (OC) pills contain estrogen and progestin that are synthetic analogs of natural hormones. These synthetic hormones affect the hypothalamus-pituitary-gonadal axis of the female reproductive system. There are many types of contraceptives; most of the OC pills prevent pregnancy by inhibiting ovulation. Estrogen and progestin are two female reproductive hormones that are critical. Typically, estradiol is produced by growing follicle (ovaries) which stimulates the hypothalamus to produce the gonadotropin-releasing hormone, which further stimulates the anterior pituitary to produce follicle-stimulating hormone (FSH) and luteinizing hormone (LH). LH production triggers the ovulation. Similarly, the progesterone is produced by corpus luteum (ovaries), which triggers the production of FSH and LH. There are many types of progesterone available. Long-term usage of synthetic estrogen and progesterone can disturb the balance between the level of these hormones in the body. This imbalance may lead to severe side effects such as breast cancer, cervical cancer, thrombosis, direct impact on the brain, and infertility. Keywords: Estrogen, Progesterone, Contraceptives, Herbal contraceptives. Â